Effectiveness of Extension Tools Among the Paddy Farmers of Tenkasi District of Tamil Nadu - Monikha, C.R.; Balasubramaniam, M.; Sukumar, J. (Indian Journal of Extension Education, 2021)
Information and communication technology (ICT) has many potential applications in delivering agricultural extension and can bring new information services to rural areas. It focuses on the enhancement of agricultural and rural development through improved information and communication processes. Present study was conducted to identify the knowledge level, skill acquisition and symbolic adoption behaviour of farmers by assessing the effectiveness of different extension tools viz., Expert system, Agri-tech portal and Extension literatures. Sixty farmers were selected from three different villages of Tenkasi District. Pretest and posttest were conducted to assess the gain in knowledge, skill acquisition and adoption of different technologies. Pretest revealed that in all the three extension tools, forty five per cent of the farmers were having high level of knowledge, while the post test results indicated that after exposure to expert system sixty per cent of the farmers acquired high level of knowledge. Similarly, 70.00 per cent of the farmers’ exposure to expert system had high level of symbolic adoption behaviour. Expert system assisted farmers to take decisions to adopt different aspects of location specific crop management practices for increasing their productivity.
Keywords: Adoption behaviour; Expert system; Knowledge level; Skill acquisition